Effective Implementation of European Community Law. A Facilitating Role of Dutch General Administrative Law - Paul ADRIAANSE; Tom BARKHUYSEN; Willemien DEN OUDEN; Ymre SCHUURMANS (Transylvanian Review of Administrative Sciences, 2008)
When discussing the influence of Community law on national law the attention often focuses on (removing) conflicts of special national provisions with European law in concrete situations. In this article, however, a different, proactive facilitating approach is chosen, focusing on general administrative law especially as a facilitating instrument for the effective implementation of European law in a broad sense: the ‘PF-method’. The central question is whether by means of general provisions of administrative law, in a proactive way, even without European law forcing to this, the legal implementation, application and enforcement of European law may be simplified and facilitated. Four topics are studied in depth: ‘fact-finding in administrative law proceedings’, ‘recovering state aid granted in breach of EC law’, ‘the division of liabilities for breach of Community law among various national authorities involved’ and ‘the embedding of the preliminary proceedings in the national law of administrative procedure’. Solutions found with regard to Dutch general administrative law may provide inspiration for other member states in search of new or alternative possibilities for implementing EC law as effectively as possible.